Sprawiedliwość międzygeneracyjna w kontekście idei rozwoju zrównoważonego - Płachciak, Adam (Annales. Etyka w Życiu Gospodarczym, 2012)
The aim of the article is an attempt of presentation the relation between intergenerational justice and the idea of sustainable development. Definitions which are related to Brundtland Report explain sustainable development as development that satisfies needs of present generations without depriving the needs of future generations. So it is clearly defined there is no mean of a short time satisfaction, but rather of a wider context – just distribution of goods and obligations (natural and financial) between generations. Thus the political decisions should concern present problems in such a way that would guaranty material as well as social foundations for further development.